Continuous subcutaneous insulin infusion therapy is associated with reduced retinopathy progression compared with multiple daily injections of insulin - Reid, Laura J.; Gibb, Fraser W.; Colhoun, Helen; Wild, Sarah H.; Strachan, Mark W. J.; Madill, Karen; Dhillon, Baljean; Forbes, Shareen (Diabetologia, 2021)
Aims/hypothesis We aimed to compare diabetic retinopathy outcomes in people with type 1 diabetes following introduction of continuous subcutaneous insulin infusion (CSII) therapy with outcomes in people receiving continuing therapy with multiple daily insulin injections (MDI). Methods This is a retrospective cohort study using the Scottish Care Information – Diabetes database for retinal screening outcomes and HbA 1c changes in 204 adults commenced on CSII therapy between 2013 and 2016, and 211 adults eligible for CSII during the same period but who continued on MDI therapy. Diabetic retinopathy progression (time to minimum one-grade worsening in diabetic retinopathy from baseline grading) was plotted for CSII and MDI cohorts using Kaplan–Meier curves, and outcomes were compared using multivariate Cox regression analysis adjusting for age, sex, baseline HbA 1c , blood pressure, cholesterol, smoking status and socioeconomic quintile. Impact of baseline HbA 1c and change in HbA 1c on diabetic retinopathy progression was assessed within CSII and MDI cohorts. Results CSII participants were significantly younger, were from less socially deprived areas, and had lower HbA 1c and higher diastolic BP at baseline. There was a larger reduction in HbA 1c at 1 year in those on CSII vs MDI (−6 mmol/mol [−0.6%] vs −2 mmol/mol [−0.2%], p < 0.01). Diabetic retinopathy progression occurred in a smaller proportion of adults following commencement of CSII vs continued MDI therapy over mean 2.3 year follow-up (26.5% vs 18.6%, p = 0.0097). High baseline HbA 1c (75 mmol/mol [9%]) was associated with diabetic retinopathy progression in the MDI group ( p = 0.0049) but not the CSII group ( p = 0.93). Change in HbA 1c at follow-up, irrespective of baseline glycaemic status, did not significantly affect diabetic retinopathy progression in either group. Conclusions/interpretation CSII was associated with reduced diabetic retinopathy progression compared with continued MDI therapy, and may be protective against diabetic retinopathy progression for those with high baseline HbA 1c . Progression of diabetic retinopathy over 3 years was not associated with a change in HbA 1c . Graphical abstract